PELAKSANAAN PEMBELAJARAN MEMBACA DAN MENULIS PERMULAAN SUATU KAJIAN ETNOGRAFI DI SD NEGERI KOTA TERNATE - Rita Samad; Samsu Somadayo; Nining Lamanca (PEDAGOGIK, 2017)
The objective of this research to describe the result of planning, presenting, evaluating, and the result of reading and writing process in SD Negeri Kota Ternate. The method of this research is descriptive qualitative. Descriptive qualitative design is giving number that happen in the class interaction. The research also is ethnography research design. Ethnography research is a research that joining some learning activities: visual (seeing), listening, speaking, thinking, and doing by different way. The Techniques of collecting data by some steps: (1) observation, (2) lock book, (3) Interview, (4) recording, and (5) evaluating. The results of the research are: (1) the planning of reading and writing learning consist of: (a) to write indicator; (b) improving and organizing the material, media, and the source of learning; (c) the scenario of learning activity planning; (d) the plan of class managing; and (e) the procedure, kinds, and evaluating instruments planning; (2) reading and writing learning process in SD Negeri Kota Ternate is the teacher did not do the steps of reading and writing, the steps pre reading and writing, process of reading and writing, and after reading and writing; (3) reading and writing learning evaluation showed that reading and writing learning planning is 67 %, conducting reading and writing learning 60 %, and learning evaluation is 64,5%.